Dosagem, in vivo, de metabólitos sanguíneos e tissulares de ratos submetidos à isquemia renal e a reperfusão durante a oferta de L-alanil-glutamina - Bezerra Filho, João Evangelista (2004)
Renal tranplantation and other operations give rise to kidney ischemia/ reperfusion injuries that may interfere with the final outcome. The purpose of this study is to examine the effects of l-alanil-glutamine pre-treatment in rats subjected to renal ischemia/reperfusion. Twenty -four rats were distributed in 4 subgroups of 6 animals. Half an hour following administation of l-alanil-glutamine (0,75 g/Kg) animals were subjected to kidney ischemia during 30 minutes. Kidney arterial blood samples were collected at the end of the ischemia and 5,15 and 30 minutes later. Glucose pyruvate lactate and cetonic bodies in vivo concentrations were determined in all samples. A second group of 24 animals received i.v.saline solution pre-treatment half an hour prior to the experiment. Laboratory analysis revealed a significant increase in blood concentration of lactate in l-alanil –glutamine group and during reperfusion. The offer of l-alanil-glutamine cause no significant change on concentration of glucose and pyruvate. On the other hand it did induce to significant reduction of cetonemia in the animal group treated with l-alanil-glutamine as compared to that observed in animals from control group. It is concluded that l-alanil –glutamine pre – treatment may enhance glycolysis during ischemia-reperfusion. Activation of malate-aspartate shuttle in glucose oxidative pathway due to increase availabitity of glutamate can explain these changes.